Understanding of the Nutri-Score front-of-pack label by Italian Medical Professionals and its effect on food choices: a web-based study on knowledge, attitudes and practices - Riccò, Matteo; Ranzieri, Silvia; Balzarini, Federica; Vezzosi, Luigi; Marchesi, Federico; Valente, Marina; Peruzzi, Simona (Acta Biomedica Atenei Parmensis, 2022)
Background and aim. A growing number of European Countries have adopted front-of-pack nutrition labels (FPNL) in order to assist costumers’ alimentary choices, and particularly Nutri-Score. While its acceptance in Italy has been slowed by ongoing debates, we assessed corresponding knowledge, attitudes and practices of a sample of Italian Medical Professionals (MP).Methods. A total of 153 MP participated into an internet-based survey by completing a structured questionnaire. While 43.1% reported any knowledge of Nutri-Score, the overall understanding of its conceptual issues was quite low (50.8% after percentual normalization of the knowledge score). Only half of participants acknowledge some usefulness of FPNL, and their acceptance as a guide for nutritional choices was seemingly low (36.6%), being more likely in MP participants from Northern regions (Odds Ratio 9.610, 95% confidence intervals 2.667-34.637), living with children < 14 year or age (3.658, 1.463-9.145), and perceiving some usefulness in FPNL (3.595, 1.381-9.356). In turn, having any knowledge of Nutri-Score and being of male gender were negative effects.Conclusions. Nutri-Score is a useful instrument in guiding consumers’ alimentary choices, but the actual understanding of its rationale by participants MP was insufficient. Specifically aimed interventions should be tailored in order to cope with a significant share of MP reporting false beliefs and misunderstanding.